Nurse champions as street-level bureaucrats: Factors which facilitate innovation, policy making, and reconstruction - Sperling, Daniel; Shadmi, Efrat; Drach-Zahavy, Anat; Luz, Shirly (Frontiers in Psychology, 2022)
Background Nurse champions are front-line practitioners who implement innovation and reconstruct policy. Purpose To understand through a network theory lens the factors that facilitate nurse champions’ engagement with radical projects, representing their actions as street-level bureaucrats (SLBs). Materials and methods A personal-network survey was employed. Ninety-one nurse champions from three tertiary medical centers in Israel participated. Findings Given high network density, high levels of advice play a bigger role in achieving high radicalness compared with lower levels advice. High network density is also related to higher radicalness when networks have high role diversity. Discussion Using an SLB framework, the findings suggest that nurse champions best promote adoption of innovation and offer radical changes in their organizations through professional advice given by colleagues in their field network. Healthcare organizations should establish the structure and promote the development of dense and heterogeneous professional networks to realize organizations’ goals and nurses’ responsibility to their professional employees, patients, and society.